Islamic Critical Thinking: The Perception of Muslim Engineering Students in Universiti Teknologi PETRONAS - M.A., Abdur-Rahman (2012)
The advocacy of Islamic concept of critical thinking to the engineering undergraduate students could eventually contribute to the emergence of professional and competent Muslim engineers who consciously adhere to the responsibility as vicegerents of Allah. The main objective of this study was to examine and analyze the perception of Muslim engineering students in Universiti Teknologi PETRONAS (UTP) towards Islamic critical thinking. A survey using a close-ended questionnaire based on the literatures on Islamic critical thinking was conducted. Data collected were analyzed using descriptive analysis. The study found that Muslim engineering students in UTP have positive perception towards and possess basic Islamic critical thinking skills. The finding suggests the importance for Muslim engineering students to be exposed to the holistic engineering education system that also emphasizes religious conceptual thought.